Dynamic data integration: a service-based broker approach. (18th September 2006) - Zhu, Fujun; Turner, Mark; Kotsiopoulos, Ioannis; Bennett, Keith; Russell, Michelle; Budgen, David; Brereton, Pearl; Keane, John; Layzell, Paul; Rigby, Michael; Xu, Jie
We address the problem of large-scale data integration, where the data sources are unknown at design time, are from autonomous organisations and may evolve. Experiments are described involving a demonstrator system in the field of health services data integration within the UK. Current web services technology has been used extensively and largely successfully in these distributed prototype systems. This paper shows that web services provide a good infrastructure layer, but integration demands a high-level 'broker' architectural layer. The first version of the demonstrator is mostly based on static linking. Lessons from this are extracted, and used to design and implement the current version, in which a more dynamic broker-based integration using service-oriented architecture, late binding and domain ontology is described.